2022
DOI: 10.1111/jse.12921
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and systematics of the tribe Sonerileae (Melastomataceae) in Africa: A revised taxonomic classification

Abstract: The tribe Sonerileae in tropical Africa and Madagascar is a morphologically diverse lineage that consists of 239 species in 10 genera. In this study, we present the first in-depth phylogenetic analysis of African Sonerileae to test monophyly of the currently recognized genera. Phylogenetic analyses were performed using sequence data from two nuclear (nrITS and nrETS) and three plastid loci (accD-psaI, ndhF and psbK-psbL). Sampling consisted of 140 accessions including 64 African, 27 Malagasy, 46 Asian, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…The utilization of multiple markers in nuclear and chloroplast DNA barcoding has not yet resolved the phylogenetic issues in Medinilla, as observed in Kartonegoro et al (2021). Furthermore, Kartonegoro et al (2021) and Veranso-Libalah et al (2022) reported that Medinilla was polyphyletic, thus requiring further intensive molecular research. The complete sequences of chloroplast ge-nomes offer a high resolution in reconstructing phylogenetic between species (Li et al 2022) and proven effective in addressing challenging phylogenetic inquiries, as an example the genus Pseudodissochaeta (Zhou et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of multiple markers in nuclear and chloroplast DNA barcoding has not yet resolved the phylogenetic issues in Medinilla, as observed in Kartonegoro et al (2021). Furthermore, Kartonegoro et al (2021) and Veranso-Libalah et al (2022) reported that Medinilla was polyphyletic, thus requiring further intensive molecular research. The complete sequences of chloroplast ge-nomes offer a high resolution in reconstructing phylogenetic between species (Li et al 2022) and proven effective in addressing challenging phylogenetic inquiries, as an example the genus Pseudodissochaeta (Zhou et al 2019).…”
mentioning
confidence: 99%
“…Out of 380 species of Medinilla sequences, only 9 species with complete plastome are now available in the GenBank, indicating that chloroplast genome data for Medinilla is still limited (Veranso-Libalah et al 2022). Medinilla tapete-magicum Cámara & Leret & Veldk.…”
mentioning
confidence: 99%